The Influence of Perception of Halal Labels and Brand Image on Cosmetic Purchasing Decisions Among Millennials - Hakim, Abdul; Sugihantoro, Hajar; Maulina, Novia; Nasichuddin, Achmad; Setiawan, Abdul Malik; Nicotiana, Diah Ayu (Indonesian Journal of Halal Research, 2024)
The cosmetics industry consistently requires up-to-date research to develop effective marketing strategies that attract consumers and build their trust. This research aims to analyze how Millennials perceive halal labels and brand image in relation to their purchasing decisions for cosmetics. The study utilized an associative research method with a quantitative approach, employing purposive sampling and a questionnaire as its instrument. Data was processed using structural equation modeling-partial least squares (SEM-PLS) analysis. The findings indicate a strong positive correlation between the perception of halal labels and Millennials' purchasing decisions for cosmetics, as halal certification is a crucial factor for this demographic. Additionally, the study found that a positive brand image also significantly influences purchasing decisions, as consumers prefer products that are recognized for their quality, safety, and popularity. The practical implications for the cosmetics industry are evident: understanding the factors that drive purchasing decisions can help companies make the best strategic choices. It is recommended that companies consistently maintain halal certification on their products and focus on building a strong brand image, as both factors play a critical role in influencing consumer decisions.